Eye disease in an onchocerciasis-endemic area of the forest-savanna mosaic region of Nigeria. - Umeh, R. E. (World Health Organization, 1996)
In a forest-saving mosaic zone of south-eastern Nigeria endemic for onchocerciasis, we identified eye disorders in 65.5% of a randomly selected population sample. Onchocerciasis-related eye disease was present in 13.7% of the study sample and constituted 21% of the total number of eye disorders. A total of 78 (33.2%) of 235 subjects with visual impairment had onchocerciasis-related eye lesions, and of 35 who were blind in both eyes, onchocerciasis-induced eye disease was the cause in 28 (80%). The prevalence of bilateral blindness from all causes in the study area was 4.1%, while that from onchocerciasis-related causes was 3.3%. The commonest onchocerciasis-induced lesions that were responsible for visual impairment and blindness were choroidoretinitis and optic nerve disease. Sclerosing keratitis, an important causative lesion in onchocerciasis-endemic savanna regions, was encountered only one. Eye disease is therefore an important feature of onchocerciasis in the forest-savanna mosaic areas of Nigeria and should be borne in mind when planning and executing control programmes.